2019
DOI: 10.3390/nu11081847
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Diet in the Stroke Belt: A Cross-Sectional Study on Adherence and Perceived Knowledge, Barriers, and Benefits

Abstract: The Mediterranean diet (MedDiet) is recommended by the current Dietary Guidelines for Americans, yet little is known about the perceived barriers and benefits to the diet in the U.S., particularly in the Stroke Belt (SB). Thus, the purpose of this study was to examine MedDiet adherence and perceived knowledge, benefits, and barriers to the MedDiet in the U.S. A cross-sectional study was conducted on 1447 participants in the U.S., and responses were sorted into geographic groups: the SB, California (CA), and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(71 citation statements)
references
References 53 publications
7
63
1
Order By: Relevance
“…In the present study, the majority of barriers reported by our sample were in relation to PBC; these included motivation, affordability, time, access and knowledge. These barriers are consistent with those previously reported for both general healthy eating [ 53 , 54 ] and towards adopting a MedDiet in non-Mediterranean countries [ 36 , 37 , 46 , 55 ]. Nevertheless, complexity of the dietary pattern, individual food preferences, and perceived additional costs were previously identified as important barriers to adherence in older Australian adults [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the majority of barriers reported by our sample were in relation to PBC; these included motivation, affordability, time, access and knowledge. These barriers are consistent with those previously reported for both general healthy eating [ 53 , 54 ] and towards adopting a MedDiet in non-Mediterranean countries [ 36 , 37 , 46 , 55 ]. Nevertheless, complexity of the dietary pattern, individual food preferences, and perceived additional costs were previously identified as important barriers to adherence in older Australian adults [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the models adjusted for factors of well-being and physical inactivity we observed a negative association between Mediterranean diet adherence and COVID-19 related deaths. Our findings that the socioeconomic factors of income and education added significantly to our models is consistent with prior work that income and education are significant factors in viral infection related hospitalization (32)(33)(34)(35) and Mediterranean diet adherence (23,(36)(37)(38)(39)(40). The finding that life satisfaction added significantly to the adjusted models is consistent with epidemiological evidence linking life satisfaction to risk of chronic disease and mortality (41)(42)(43).…”
Section: Discussionsupporting
confidence: 90%
“…The purpose of psychoeducation on caregivers is to increase understanding of family members to disease journey, reduce recurrence of stroke, and increase family and client roles [20]. Psychoeducation given to families can significantly reduce anxiety and burden of caregivers especially when the patients were treated at hospital [21].…”
Section: Discussionmentioning
confidence: 99%